2020
DOI: 10.1093/pm/pnaa034
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functional Therapy for People with Nonspecific Persistent Low Back Pain in a Secondary Care Setting—A Propensity Matched, Case–Control Feasibility Study

Abstract: Background Effective, inexpensive, and low-risk interventions are needed for patients with nonspecific persistent low back pain (NS-PLBP) who are unresponsive to primary care interventions. Cognitive functional therapy (CFT) is a multidimensional behavioral self-management approach that has demonstrated promising results in primary care and has not been tested in secondary care. Objective To investigate the effect of CFT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A significant improvement was found in pain and function in the LBP group with large effect sizes similar to what has been demonstrated previously when employing a patient-centered approach to managing LBP 15,32. Moreover, the improvement in pain and disability were noticeably better than what is considered clinically meaningful 33,34.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A significant improvement was found in pain and function in the LBP group with large effect sizes similar to what has been demonstrated previously when employing a patient-centered approach to managing LBP 15,32. Moreover, the improvement in pain and disability were noticeably better than what is considered clinically meaningful 33,34.…”
Section: Discussionsupporting
confidence: 82%
“…A significant improvement was found in pain and function in the LBP group with large effect sizes similar to what has been demonstrated previously when employing a patientcentered approach to managing LBP. 15,33 Moreover, the improvement in pain and disability were noticeably better than what is considered clinically meaningful. 34,35 However, these improvements were not aligned with changes in pain sensitivity similar to recent findings by Vaegter et al 36 Arguably, the initial symptoms, experienced immediately after the onset of clinical LBP, could reflect tissue injury.…”
Section: A Successful Rehabilitation Strategymentioning
confidence: 94%
“…Following the exclusion of specific causes of LBP, CFT targets modifiable cognitions, emotions, movements, postures and lifestyle factors identified to contribute to an individual's ongoing pain and activity limitation (O'Sullivan et al, 2018 ). CFT has shown clinically significant and sustained improvements in pain and function (O'Sullivan et al, 2015 ; Ussing et al, 2020 ; Vibe Fersum et al, 2013 ; Vibe Fersum et al, 2019 ) and is often accompanied by changes in the way people conceptualize their pain (Bunzli, McEvoy, et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…CFT has shown clinically significant and sustained improvements in pain and function (O'Sullivan et al, 2015;Ussing et al, 2020;Vibe Fersum et al, 2013;Vibe Fersum et al, 2019) and is often accompanied by changes in the way people conceptualize their pain (Bunzli, McEvoy, et al, 2016). Four specially trained physiotherapists provided up to 10 sessions of funded CFT depending on the participants' clinical course.…”
Section: Interventionmentioning
confidence: 99%
“…However, the high risk of attrition bias and performance bias precluded the confirmation of the CFT effectiveness for disability. Ussing et al 29 found that CFT was feasible and displayed clinically important effects for chronic low back pain in a secondary care setting. However, the participants were not randomised.…”
Section: Introductionmentioning
confidence: 99%